Partial Purification and Characterization of Urease from Red Lentils (Vicia lens (L.) Coss. & Germ.) - Zusfahair, Zusfahair; Ningsih, Dian Riana; Bilalodin, Bilalodin; Fatoni, Amin; Setiawan, Ely; Sulistyowati, Aris (Molekul, 2025)
ABSTRACT. Urease is an enzyme that catalyzes the hydrolysis of urea into ammonia and carbon dioxide. A significant application of urease is found primarily in food, medical equipment and biosensor industries. This research aims to analyze the amino acid content of red lentil seeds and the extraction, purification, and characterization of urease from red lentils. The study started by analyzing the amino acid content in red lentil seeds using High-Performance Liquid Chromatography (HPLC). The red lentil seeds were extracted using phosphate buffer pH 7.0 and separated using centrifugal separation technique until crude extract of urease was produced. The crude extract of urease was then concentrated using acetone at varied saturation level (33, 41, 50, 60, and 67%). The fraction with the highest specific activity was then analyzed using SDS-PAGE method and characterized for its pH, incubation temperature, and substrate concentration against the urease activity. The urease activity was determined using Nessler method. The research results showed that red lentils seeds contained all essential amino acids. The highest specific activity was found in the fraction at 50% acetone saturation level (F50) and purity level 6.3 times than the crude extract. The characterization result indicated that F50 was purer than the crude extract. The optimum urease activity of crude extract and F50 was obtained at pH 7.0 and an incubation temperature of 35 °C. The KM value of F50 was lower than crude extract. F50 has a higher affinity for binding to substrates so that the enzyme has higher efficiency in forming the products. Urease from red lentil seeds concentrated using acetone was 50% more potent as a catalyst than the crude extract. The research data will be the basis for the application of this urease. Keywords: Acetone, characterization, partial purification, red lentil, urease